Student Paradigm Analysis of Entrepreneurship Post-Pandemic in Indonesia - Harti Harti; Lucky Rachmawati; Norida Canda Sakti; Susanti Susanti; Luqman Hakim; Albrian Fiky Prakoso; Bayu Surindra; Arina Salsabilla Haq (International Journal of Emerging Research and Review, 2023)
Objective: The outbreak of COVID-19 has had a significant impact on Indonesia's economy as a whole. The implementation of social distancing measures and subsequent Large-Scale Social Restrictions (LSSR) have led to companies downsizing and employees working from home. This has had a negative effect on the output of these companies and has necessitated action by the government to accelerate the recovery of all economic sectors. This study provides an overview of the student paradigm of entrepreneurship with a focus on the key variables of entrepreneurship education components, facilities and infrastructure, and entrepreneurial intention. Additionally, the study aims to explore the influence of these variables on entrepreneurial intention and to provide recommendations from student problem. Method: This research employs a quantitative and objectives addressed using two data analysis techniques: descriptive analysis and multiple linear regression analysis. Results: The findings of this study indicate that entrepreneurship education has a positive and significant influence on entrepreneurial intention, as do facilities and infrastructure. Additionally, the study found that entrepreneurship education and facilities and infrastructure both have a positive and significant influence on entrepreneurial intention. Novelty: The focus of this research involves master's degree students which are still little researched because most previous research has examined undergraduate students or the general public.